ANALISIS RESIKO USAHATANI IKAN BANDENG DI DESA SUNGAI UNDANG KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN KALIMANTAN TENGAH - Lili Winarti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
This study aimed to analyze the price risk, production risk and the risk income of milkfish farming in Sungai Undang village Seruyan Hilir Subdistrict Seruyan. The method is performed in a census sampling method to fish farmers with the number of respondents 29 fish farmers who all fish sampled in this study. Analysis of the data used is the analysis of qualitative and quantitative analysis, qualitative analysis performed to obtain a picture or descriptive farming milkfish and quantitative analysis to analyze the risks of farming to determine the density of the probability distribution and risk assessment can be done by measuring the deviations that occur, some the size of which can be deviation used to measure them are variants (variance), standard deviation (Standard deviation), the coefficient of variation (variation coefficient) and a lower limit value (L). The results of the risk analysis showed that fish farming price risk CV values> 0.5 (0.10> 0.5) and lower limit value for the risk of the price of Rp 8,162.18 / kg, seen from production risks CV values> 0.5 (0 , 13> 0.5) and lower limit value for the production of 1,224.90 kg, and the views from the income risks Cv values> 0.5 (0.34> 0.5) and lower limit value for the revenue of Rp 1,874,420.77 / kg and from all the risks studied fish farming fish businesses have the value of the price, production and income is still above the lower limit of risk faced, this indicates that the business is still profitable fish farmers and viable seen from risk analysis efforts.